Exploring the Therapeutic Benefits of Quranic Verses in Managing Anxiety Associated with Physical Illnesses - Rohollah Saranjam; Ali Massoudifar; Aman Allh Zamani; Fereshteh Jafariyan (Iranian Journal of Educational Research)
Objective: This study investigates the methodologies for overcoming anxiety through spiritual therapy, specifically focusing on the teachings of the Qur'an. It explores how spirituality, as outlined in religious texts, can provide strategies for alleviating anxiety and fostering inner peace. Methods: A descriptive approach was employed to examine spiritual therapy, with particular emphasis on the Qur'an’s insights into the nature of anxiety and its remedies. The study considers both psychological perspectives and Islamic teachings, categorizing the methods into insight-based and behavioral approaches. Results: The Qur'anic approach to anxiety emphasizes two primary methods: insight methods, which include religious and mental spirituality, belief systems, and understanding the purpose of suffering; and behavioral methods, such as the remembrance of God, prayer, trust, piety, and belief in God and the Resurrection. These methods were found to play crucial roles in alleviating anxiety and promoting peace. Conclusions: Spirituality, particularly as taught in the Qur'an, serves as a foundational tool for human tranquility. By integrating cognitive and behavioral strategies, individuals can overcome anxieties arising from material deficiencies. Further research into the role of spirituality across different religious practices is needed to deepen the understanding of its impact on mental well-being.